Orthorexic eating behavior in patients with somatoform disorders - Barthels, Friederike; Müller, Romina; Schüth, Tobias; Friederich, Hans-Christoph; Pietrowsky, Reinhard (Eating and weight disorders, 2019)
Although anecdotal reports suggest a relation between orthorexic eating behavior and symptoms of somatoform disorders, this issue has not yet been investigated. The aim of this study was to compare orthorexic eating behavior and other characteristics of disordered eating behavior in patients with somatoform disorders to a sample of healthy controls.